Microfinance Credit and Financial Performance of Small and Medium Enterprises in Wakiso Town Council, Wakiso District - Kantono, Maureen; Kijjambu , Frederick (Student’s Journal of Health Research Africa, 2025)
Background Despite widespread access to microfinance services in Wakiso Town Council (WTC), over 73% of Small and Medium Enterprises (SMEs) report poor financial performance. This study investigated the relationship between microfinance credit and SME financial performance in WTC, Wakiso District, Uganda. Methods A cross-sectional design was used to collect primary data from 277 SMEs using structured questionnaires, supplemented with secondary data from WTC financial records. Financial performance was assessed through profitability (ROA), liquidity, and solvency indicators. Pearson correlation and regression analysis were conducted using SPSS v29. Results Most SMEs (57.8%) had been operational for less than 5 years, and 61.7% relied on microfinance institutions for funding. Correlation analysis showed a weak negative association between access to microloans and profitability (r = -0.128, p = 0.033), but a positive correlation between effective use of microloans and profitability (r = 0.181, p = 0.003). Satisfaction with loan terms showed a negative correlation with profitability (r = -0.124, p = 0.039). High borrowing frequency was positively associated with improved solvency (r = 0.122, p = 0.043). Regression analysis revealed that microfinance credit variables accounted for 7.7% of the variance in SME financial performance (R² = 0.077, F(8, 268) = 2.783, p = 0.006). Conclusion Access to microloans alone does not significantly enhance SME profitability in WTC. Overborrowing and rigid loan conditions may undermine benefits. Effective loan utilization and tailored financial literacy interventions are essential to strengthen SME financial performance. Recommendations Stakeholders should revise loan structures to include flexible terms, monitor credit use, and implement financial literacy programs to help SMEs maximize microfinance benefits.